Community Service Initiative on Scientific Writing: Implementing Scaffolding to Enhance Academic Article Development - Nurtanto, Muhammad; Rohmatulloh, Rohmatulloh; Kholifah, Nur (Information Technology and Science (ITScience), 2024)
This community service program aimed to enhance the scientific writing skills of Ministry of Energy and Mineral Resources (MEMR) employees, enabling them to transform performance reports into academic publications. Using the Participatory Action Research (PAR) approach, the program identified challenges and implemented structured solutions through scaffolding techniques. Conducted at the Human Resource Development Agency for Energy and Mineral Resources (HRDA-EMR) in Bandung, the program involved 24 participants from eight divisions. The implementation consisted of three phases: preparation, execution, and evaluation. The preparation phase analyzed participants’ characteristics to ensure equitable group distribution. The execution phase applied scaffolding across four stages: identifying relevant literature, understanding research methodologies, structuring article components, and developing detailed narratives. Each stage incorporated guidance, hands-on assignments, and peer discussions to support participants' learning process. The evaluation phase measured participants' competency improvements and the program’s effectiveness. Results demonstrated a significant increase in participants’ academic writing abilities, as evidenced by completed and submitted articles. The scaffolding approach effectively addressed individual challenges, promoted critical thinking, and facilitated gradual skill development. This program highlights the potential of scaffolding in enhancing academic writing skills across various professional fields. Future programs should consider integrating digital tools and emphasizing post-submission strategies to better prepare participants for global scientific engagement.